Scientific epistemology an introduction - Kornblith, Hilary (Oxford University Press, 2021)
"This book provides an introduction to a scientifically informed approach to epistemological questions. Theories of knowledge are often motivated by the need to respond to skepticism. The skeptic presents an argument which seems to show that knowledge is impossible, and a theory of knowledge is called upon to show, contrary to the skeptic, how knowledge is indeed possible. Traditional epistemologies, however, do not draw on the sciences in providing their response to skepticism. The approach taken here, however, shows how an epistemology which is informed by the sciences offers an especially illuminating understanding of the nature of knowledge and what makes it possible. Along the way, a distinctive methodology for philosophy is defended, as is an approach to understanding how inference is conducive to knowledge which highlights various structural similarities between the workings of our perceptual systems and native inferential mechanisms. A perspective on the human capacity to reflect on our beliefs is defended which highlights its importance in cooperative problem solving"--
Keywords: Erkenntnistheorie; Wissenschaft; Philosophy and science; Science / Philosophy; Knowledge, Theory of